2009
DOI: 10.1186/1742-4690-6-16
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G induces a hypermutation gradient: purifying selection at multiple steps during HIV-1 replication results in levels of G-to-A mutations that are high in DNA, intermediate in cellular viral RNA, and low in virion RNA

Abstract: These results suggest that sublethal levels of hypermutation coupled with purifying selection at multiple steps during the early phase of viral replication lead to the packaging of largely unmutated genomes, providing a mechanism by which mutant Vif variants can persist in infected individuals. The persistence of genomes containing mutated gag genes despite this selection pressure indicates that dual infection and complementation can result in the packaging of hypermutated genomes which, through recombination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 49 publications
6
70
0
1
Order By: Relevance
“…This robust system was used for identification of residues critical for Vif1-APOBEC3 interactions (34, 40) that we subsequently confirmed in both T cell lines and primary CD4 ϩ T cells (41,65). A summary of the Vif2 interactions with human A3G and A3F and their comparison to previously determined Vif1 interactions are shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This robust system was used for identification of residues critical for Vif1-APOBEC3 interactions (34, 40) that we subsequently confirmed in both T cell lines and primary CD4 ϩ T cells (41,65). A summary of the Vif2 interactions with human A3G and A3F and their comparison to previously determined Vif1 interactions are shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of the preceding sections demonstrate that APOBEC3 packaged into MMTV virions retains functional deaminase activity, we previously showed that integrated MMTV proviruses found in wild-type mice showed no mutagenic hallmarks of cytidine deamination compared to knockout mice (25). However, uracil-containing reverse-transcribed DNA is able to be degraded in cells prior to integration into the host genome or prevented from integration (42), which would account for the absence of G-to-A mutations in integrated MMTV proviruses. We thus next tested whether ex vivo reversetranscribed MMTV DNA made from viruses containing packaged APOBEC3 underwent cytidine deamination.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of retroviral replication by A3G is at least partially attributable to the targeted deamination of cytosine in the retroviral cDNA (3,39), which has multiple potential effects upon viral infection. First, it may subject the cDNA to DNA repair pathways that could ultimately degrade the viral genome, although it is unclear if classic base excision repair pathways play a role (40).…”
Section: Loop Graft Variants Effectively Restrict Hiv-bhagwat and Co-mentioning
confidence: 99%